(untitled) (Cadernos de Sociomuseologia, 2020)
Madalena Braz Teixeira Departamento de Museologia, Universidade Lusófona de Humanidades e Tecnologias Tese de Doutoramento PhD (2019) Abstract This work aims at giving an historical perspective about the evolution of the National Costume Museum – Monteiro-Mór Park, since its creation in December 1976 to the present day. However, the landmarks for this study are situated between the inauguration of the museum, which occurred on July 26-1977 and my retirement on April 19-2008. The existence of the Monteiro-Mór Park, as an integral part of the territory encompassed by the National Costume Museum, represents an intrinsic part of the body encompassed by this museological institution. In its global profile, it is the equivalent of an eighteenth century leisure property (Quinta de Recreio). In this sense, it was considered essential to reflect upon its dual situation derived from both the unity and the multiplicity of its functions, even the plurality of these, which the Monteiro-Mór Park as a whole can and should develop. The activity carried out by this institution for over thirty years was conducted by three headships, the last being my responsibility, between 1983 and 2008. In this sense and focusing on the twenty-five year period during which I directed this museum, I proceeded to present this institution, to characterize it, as well as examining the dynamics of its exhibition programs. I defend that the analytical model I applied in the in-depth study of the two hundred and sixty one exhibitions held at the museum, allows for the conclusion that the fundamental guideline of this programming endeavour reflects, from the beginning, an orientation strongly centred in the main museological function, exhibition, within the field of Social Museology. Beside those exhibitions, there were presented plus two hundred and twenty-five exhibitions in mainland Portugal, Madeira and the Azores, as well as eighteen exhibitions taken abroad. These exbitions taken as a whole of five hundred and four which reflects the domination of exhibitions as the fundamental guideline in order to enlarge a global extention of the Museu Nacional do Traje. On the other hand, the long term practice and the reflection now developed regarding the work carried out has led me to the elaboration of a proposal in the field of Social Museology, to be applied to the whole of the Paço do Lumiar territory. This proposal develops the idea of Paço do Lumiar as a Cultural Satellite of Lisbon. This concept is understood here as “overflowing” from the museological institutions existing in that area, functioning as a cohesive element for the plural neighbourhood of the differentiated organisations, both public and private. The aim being to underline the memory and the identity reflected by this toponymy that is centuries old, of Medieval origin, still functioning to this day as a focal centre for the social fabric of Paço do Lumiar, as an urban reality and the oldest parishe of the city of Lisbon. Keywords: Museum, Museology, New Museology, Sociomuseology, Exhibition,